2018
DOI: 10.7748/nr.2018.e1533
|View full text |Cite
|
Sign up to set email alerts
|

Core story creation: analysing narratives to construct stories for learning

Abstract: Stories constructed from raw narratives in the context of constructivism can provide a medium or an 'end product' for use in learning resource development. This can then contribute to educating students or health professionals about patients' experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…Narrative inquiry does not end in telling stories (Bell, 2002). It includes both how and what of a phenomenon (Petty, Jarvis, & Thomas, 2018). Stories from the three EFL researchers help us gain a deeper understanding of how the negative emotions are experienced (Johnson 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Narrative inquiry does not end in telling stories (Bell, 2002). It includes both how and what of a phenomenon (Petty, Jarvis, & Thomas, 2018). Stories from the three EFL researchers help us gain a deeper understanding of how the negative emotions are experienced (Johnson 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The audio recorded interview with Akash was later transcribed and converted into a story by the researchers (Petty, Jarvis, & Thomas, 2018). After constructing the story of field experiences we recursively read the text till code saturation was achieved (Saunders, Sim, Kingstone, Baker, Waterfield, Bartlam, Burroughs, & Jinks, 2018).…”
Section: Methodology Of Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Each interview yielded raw narrative transcripts which were reconfigured to create a coherent plot in storied, chronological form. The actual process of core story creation is the subject of a separate published paper (Petty, Jarvis, & Thomas, ) . Second, thematic analysis followed the story creation, congruent with the aforementioned work by Rossman et al () where the actual stories from participants were used for the basis of analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In this main study, parents were interviewed to collect their stories about their experience of having a premature baby through the neonatal unit and beyond and comprised two overarching components: Firstly, what the parents experienced through their neonatal trajectory to inform learning resources using their narratives is to be published separately (pending). The methodological approach to story creation used in this part of the study has also been reported previously (Petty et al, 2018). The second component, and the focus of this paper yet to be reported, is an exploration of what learning students and staff can draw from the experiences of parents themselves.…”
Section: Introductionmentioning
confidence: 99%